The Influence of Corporate Political Connections and Family Ownership on Audit Quality - Erisi, Tasya; Dwita, Sany; Raga, Ridha Azka; Hayati, Dian Indah (Universitas Negeri Padang, 2025)
Purpose – This study aims to examine and provide empirical evidence regarding the influence of corporate political connections and family ownership on audit quality with return on assets, leverage, and public accounting firm size as control variables.Design/methodology/approach – This study uses a quantitative approach. The population in this study includes SOEs and conglomerate companies listed on the Indonesia Stock Exchange in 2021-2023. Samples were taken using a purposive sampling method. The analysis method used is multiple linear regression analysis.Findings – The results of this study found that corporate political connections and family ownership have no significant effect on audit quality. Audit quality is influenced by the control variable, public accounting firm size.Originality/value – This study contributes to the audit quality literature in several ways. First, research that explores the variables of political connections and family ownership in the context of audit quality is still limited. Second, previous studies regarding the influence of political connections and family ownership on audit quality in Indonesia used input-based measurements, such as auditor choice as a proxy for audit quality. In this study, the audit quality measurement used is output-based, which is based on financial reporting quality measured using earnings quality (discretionary accruals) which is more relevant to be applied in Indonesia, considering that Indonesia is a country with a high level of opacity of corporate earnings. Third, previous studies use dummy variables to indicate whether a company has political connections, so the variation in the strength of connections is less revealed. In this study, political connections are measured using an index score of political connections with various levels of positions in the bureaucracy.Research limitations/implications – This research was only conducted on SOEs and conglomerate companies listed on the IDX; therefore, the research results cannot be generalized to other sectors/types of companies. The period in this study is still relatively short, which is only limited to a span of 3 years from 2021-2023. Future research can expand the research sample size, including all companies listed on the IDX, and extend the observation period to obtain more comprehensive results.Keywords: Corporate Political Connections, Family Ownership, Audit QualityArticle Type: Research Paper